PENGARUH KREATIVITAS GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS VII PADA MATA PELAJARAN PAI & BP DI SMP PLUS DAARUL JANNAH KABUPATEN TANGERANG - Al Irsyadiyah (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2021)
The purpose of the study was to determine the effect of teacher creativity on the learning motivation of class VII students at SMP Plus Daarul Jannah, Tangerang Regency. This type of research is field research using a quantitative approach with 30 respondents. The results of this study concluded that the value of the frequency distribution of teacher creativity (variable X) 80% of 24 students from 30 respondents, the value of the frequency distribution of learning motivation (variable Y) 73.33% and the magnitude of the influence of teacher creativity on learning motivation obtained linear regression values Sig < 0.05, namely 0.002 < 0.05, then Ho is rejected, meaning that the independent variable (X) of teacher creativity significantly affects the variable (Y) namely student learning motivation. Based on the value of R square is also called the coefficient of determination which in this case means that the variable of learning motivation is influenced by the creativity of the teacher by 28.3%. The remaining 71.7% is influenced by other factors that have not been studied in this study.